Case report: Targeted sequencing facilitates the diagnosis and management of rare multifocal pure ground-glass opacities with intrapulmonary metastasis - Yang, Yingshun; Pei, Guotian; Li, Mingwei; Ma, Xiaoxue; Wang, Shuai; Min, Xianjun; Meng, Shushi; Qin, Jiayue; Wang, Huina; Liu, Jun; Huang, Yuqing (Frontiers in Oncology, 2024)
Treatments for multiple ground-glass opacities (GGOs) for which the detection rate is increasing are still controversial. Next-generation sequencing (NGS) may provide additional key evidence for differential diagnosis or optimal therapeutic schedules.We first reported a rare case in which more than 100 bilateral pulmonary GGOs (91.7% of the GGOs were pure GGOs) were diagnosed as both multiple primary lung cancer and intrapulmonary metastasis. We performed NGS with an 808-gene panel to assess both somatic and germline alterations in tissues and plasma. The patient (male) underwent three successive surgeries and received osimertinib adjuvant therapy due to signs of metastasis and multiple EGFR-mutated tumors.The patient had multiple pure GGOs, and eight tumors of four pathological subtypes were evaluated for the clonal relationship. Metastasis, including pure GGOs and atypical adenomatous hyperplasia, was found between two pairs of tumors. Circulating tumor DNA (ctDNA) monitoring of disease status may impact clinical decision-making.Conclusions: Surgery combined with targeted therapies remains a reasonable alternative strategy for treating patients with multifocal GGOs, and NGS is valuable for facilitating diagnostic workup and adjuvant therapy with targeted drugs through tissue and disease monitoring via ctDNA.